МЕТОДЫ И ПРАКТИКА ОЦЕНКИ НАЦИОНАЛЬНОЙ ЛОГИСТИЧЕСКОЙ СИСТЕМЫ РЕСПУБЛИКИ КАЗАХСТАН - O. .. Sabden; G. M. Imasheva; A. T. Moldabekova (Экономика: стратегия и практика, 2018)
The purpose of this study is to study the theoretical and methodological approaches to assess the logistics system of the state and, on the basis of this, develop a methodology for researching the national logistical system of the Republic of Kazakhstan. The article considers theoretical and methodological approaches to the assessment of the macro-logistic system. A brief overview of the international logistics indexes was made, the place of Kazakhstan in these ratings was indicated. It is substantiated that one of the most important methods for the integrated assessment of the logistics system is the expert interview method and developed the indicators, the sample structure of the respondents to assess the national logistics system of the Republic of Kazakhstan. This work can be applied in studies to identify problems and prospects for the development of national logistics systems. In the course of the research, the authors used methods such as comparative analysis and a systematic approach.